Community-level environmental characteristics predictive of childhood stunting in Bangladesh - a study based on the repeated cross-sectional surveys. Issue 3 (4th March 2022) - Khan, Jahidur Rahman; Hossain, Md. Belal; Awan, Nabil
ABSTRACT: Coastal morphology makes Bangladesh vulnerable to environmental hazards and climate change. Therefore, environmental characteristics may shape population health, including child health. The prevalence of stunting among under-five aged (U5) children is high in Bangladesh. However, there is a lack of research on environmental predictors of stunting. This study aimed to assess the association between community-level environmental characteristics and stunting using pooled data from the three latest Bangladesh demographic and health surveys (BDHS). According to the multilevel model, rainfall, distance to protected areas, and vegetation index showed a nonlinear association with stunting. The temperature was inversely, and distance to water bodies was positively related to stunting. Overall, results evidence the environmental characteristics are predictive of stunting, and these characteristics should be taken into account during intervention design to minimise the negative effects of environmental change on child health. Further research is also necessary to comprehend the causal pathways between environmental characteristics and stunting in Bangladesh.